El arte y los centros de memoria como estrategia de reparación integral a víctimas de violaciones de derechos humanos - Poveda Yánez, Jorge Medardo (2018)
Remedies and reparations for severe human rights violations is a concept that required a progressive path to consolidate, going from the merely monetary to incorporate other aspects related to the immaterial repercussions of this type of crimes. This has led to a legal institution internationally proven as ideal to face gross or serious violations of human rights, not only for the recovery of the victims’ affected properties, but repairing, in an integral way, the lives interrupted by the systematic violence, in those cases it is compulsory to construct memory, it is a right that society has in order to establish and protect its own history, in an effort to prevent future human rights violations. Understanding memory as a right, is the perspective that the present investigation uses to link integral reparations with art, as an accurate resource to perform the symbolic reparations and the rest of the satisfaction remedies that lead to the moral recovery of the victims and their families. Because of the power that art has to transform, it constitutes an answer for the victims, changing reality through images with aesthetic value capable of confronting the past and the present in a dialectic way, with the intention of restoring the honor, recovering the reputation, rescuing the truth, building the memory and at last, to socially achieve justice in a form that no verbal speech can do. Since the author of the current investigation is also a professional artist, this thesis is going to be accomplished in a multidisciplinary way; deducing the legal ramifications of the State obligations towards its own citizens, when in case of gross or systematic violations of human rights, while identifying how art can help to achieve them.